Low-Frequency Variability of the Yellow Sea Cold Water Mass Identified from the China Coastal Waters and Adjacent Seas Reanalysis. (6th August 2015) - Li, Xuewei; Wang, Xidong; Chu, Peter C.; Zhao, Dongliang
Abstract : This study uses the China Coastal Waters and Adjacent Seas Reanalysis (CORA) data to investigate the interannual and decadal variability of the Yellow Sea cold water mass (YSCWM) and its relationship to climate indices including the Arctic Oscillation (AO), El Niño/Southern Oscillation (ENSO), and Pacific Decadal Oscillation (PDO). On the interannual timescale, the strong correlation between winter PDO and the YSCWM may indicate the dominant effect of winter PDO on the YSCWM through the modulation of local heat flux and wind stress. It is also found that the local wind stress and heat flux in summer have little impact on the interannual variability of the YSCWM. On the decadal time scale, the YSCWM is associated with winter AO and winter PDO. Winter AO mainly controls local heat flux, modulating the decadal variability of the YSCWM. In contrast, winter PDO is strongly connected with winter heat flux and wind stress to modulate the decadal variability of the YSCWM. In summer, for three climate factors, ENSO is the dominant factor controlling the decadal variability of the YSCWM.